Compensation for earnings risk under worker heterogeneity - Peter Berkhout; Joop Hartog; Dinand Webbink (Institute for the Study of Labor (IZA), 2006)
We use two large Dutch datasets to estimate the Risk Augmented Mincer equation and test for risk compensation in expected earnings. We replicate earlier findings of a positive premium for risk and a negative premium for skew and add confirmation of the key results if we control for individual ability. We find that immigrants have graduated in more risky educations but obtain identical risk compensation. Among recent graduates, women receive higher risk compensation than men, consistent with their higher risk aversion, while for a labour force cross-section, lower average compensation for women is consistent with their presence in less risky educations. Lower average compensation for vocational graduates than for university graduates is consistent with presumed higher risk aversion and lower observed risk.
Keywords: J31; 330; wages; risk; earnings function